2010
DOI: 10.1038/cr.2010.174
|View full text |Cite
|
Sign up to set email alerts
|

Lysine methylation of promoter-bound transcription factors and relevance to cancer

Abstract: p53, NFκB, STAT3, and several other transcription factors are reversibly methylated on lysine residues by enzymes that also modify histones. The methylations of NFκB and STAT3 take place when they are bound to promoters, suggesting a more general model in which the binding of inducible transcription factors to DNA helps to recruit chromatin-modification machinery, which then may modify not only histones but also the bound transcription factors. Mutations of some histone-lysine methyltransferases and demethylas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 56 publications
0
57
0
Order By: Relevance
“…Lysine methylation by histone-modifying enzymes activates several different transcription factors, including STAT3, p53, and NF-κB, that have well-recognized roles in tumorigenesis. Therefore, mutations, amplifications, or deletions of histone lysine methyltransferases and demethylases that also modify transcription factors may affect cancer development and progression significantly (14). For this reason, these enzymes are promising targets for antitumor drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lysine methylation by histone-modifying enzymes activates several different transcription factors, including STAT3, p53, and NF-κB, that have well-recognized roles in tumorigenesis. Therefore, mutations, amplifications, or deletions of histone lysine methyltransferases and demethylases that also modify transcription factors may affect cancer development and progression significantly (14). For this reason, these enzymes are promising targets for antitumor drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Stark et al (14,15) show that gene-specific inducible modifications of transcription factors occur at promoters, where the local chromatin machinery is active, and that these modifications can modulate the local functions of the transcription factors by altering their stability, transactivation potency, and affinity for DNA, in turn affecting the strength and duration of inducible gene expression. Therefore we tested whether EZH2, the enzyme responsible for K49 dimethylation of STAT3, inhibits STAT3 binding to the SOCS3 promoter.…”
Section: Stat3mentioning
confidence: 99%
See 1 more Smart Citation
“…The docking site for SET9 is provided by the phosphorylated S727 residue of STAT3, because the S727A mutant of STAT3 fails to recruit SET9 to the promoter. We reviewed several additional examples of the lysine methylation of promoter-bound transcription factors (Stark et al 2011). Our working hypothesis, which needs to be tested further, is that the promoter-bound factor provides a docking site for a histone-modifying enzyme that then catalyzes functionally important modifications, not only of the transcription factor but potentially also of local histones and the transcriptional machinery itself.…”
Section: Lysine and Arginine Modificationsmentioning
confidence: 99%
“…Recently, Ray et al (8) reported that STAT3 mono-ubiquitination at Lys-97 is a key mediator of BRD4-dependent antiapoptotic and pro-proliferative gene expression. Several transcription factors, including STAT3, NF-B, 2 and p53, are reversibly methylated on lysine residues by histonemodifying enzymes, with profound consequences for their functions (9). STAT3 is methylated on Lys-140 and Lys-180 by the histone methyl transferases SET9 and EZH2, respectively (10,11).…”
mentioning
confidence: 99%